2009
DOI: 10.1002/fld.2004
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of IDEAL algorithm for three‐dimensional incompressible fluid flow and heat transfer problems

Abstract: SUMMARYRecently, an efficient segregated algorithm for incompressible fluid flow and heat transfer problems, called inner doubly iterative efficient algorithm for linked equations (IDEAL), has been proposed by the present authors. In the algorithm there exist inner doubly iterative processes for pressure equation at each iteration level, which almost completely overcome two approximations in SIMPLE algorithm. Thus, the coupling between velocity and pressure is fully guaranteed, greatly enhancing the convergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Supporting the findings of Sun et al, 14 IDEAL was found to allow a higher relaxation factor than SIM-PLER and resulted in less iterations to convergence. However, the modest increase in relaxation factor and reduced iterations were nearly offset by the increased computational cost required by IDEAL using the given number of corrector iterations.…”
Section: Va1 Geometry and Boundary Conditionssupporting
confidence: 82%
“…Supporting the findings of Sun et al, 14 IDEAL was found to allow a higher relaxation factor than SIM-PLER and resulted in less iterations to convergence. However, the modest increase in relaxation factor and reduced iterations were nearly offset by the increased computational cost required by IDEAL using the given number of corrector iterations.…”
Section: Va1 Geometry and Boundary Conditionssupporting
confidence: 82%
“…The first benchmark-quality solution on the three-dimensional flow at Re= 10 3 was reported by Albensoeder and Kuhlmann. 20 More recently threedimensional steady flows were computed by Turner et al 21 for Re number up to Re= 865 and by Sun et al 22 for Re= 1000 mainly for the purpose of code verification.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical benchmark data for a Reynolds number of 1000 in a cubic lid driven cavity were reported by Albensoeder and Kuhlmann [2] using a Chebyshev-collocation in space and Adams-Bashforth backward-Euler scheme in time. Steady state results were reported for a Reynolds number of 865 and 1000 respectively by Tuner et al [43] and Sun et al [40] in the code verification and validation studies. Recently, Feldman et al [11] numerically predicted the onset of oscillatory instability in a three-dimensional lid driven flow in a cubic cavity and found that the oscillatory instability of the flow sets in via a symmetry-breaking sub-critical Hopf bifurcation approximately at a Reynolds number of 1914.…”
Section: Introductionmentioning
confidence: 99%